A Case of (Decreasing) American Exceptionalism: Single-Family Zoning in the United States, Australia, and Canada. Issue 3 (3rd July 2022) - Whittemore, Andrew H.; Curran-Groome, William
Abstract: Problem, research strategy, and findings: Today, the United States stands alone among high-wealth countries in its copious use of exclusive zoning for single-family detached homes (single-family zoning, SFZ). Australia and Canada, however, are two countries that mirrored U.S. practices through the mid-20th century, and these countries still have SFZ, though it is less widespread today. We theorized reasons for the United States' divergence in a review of histories and other studies from the three countries. We observed that when fiscal, affordability, and environmental concerns took hold globally in the 1970s, Australian and Canadian governments addressed these issues in part by opening single-family areas to more housing types, whereas nearly all U.S. governments left SFZ unchallenged. We show here how historical racial composition and prejudice in the United States, though long intertwined with zoning practices, began to distinguish American residential zoning practice from its Canadian and Australian counterparts at this time, explaining that American planners faced revanchism in the wake of civil rights legislation and White flight. A recent flurry of reform in the United States, however, indicates that U.S. residential zoning practices are reconverging with those in Australia and Canada. Takeaway for practice: Observing how American zoning paralleled and then diverged from its Australian and Canadian counterparts has revealed another way in which U.S. racial composition and prejudice have distinguished the climate of planning in the United States. We also demonstrate how a more equitable way of zoning, one that opens more urban land to housing mixture, can provide a basis for building more sustainable cities in the United States. As American zoning begins to reconverge with its Australian and Canadian counterparts, U.S. planners can look to these countries to understand the potential and limits of undoing SFZ in pursuit of environmental, fiscal, and housing goals.